WT1表达对急性白血病异基因造血干细胞移植预后的影响 (Zhonghua Xue Ye Xue Za Zhi, 2018)
OBJECTIVE: To study the effect of WT1 expression on the prognosis of allogeneic hematopoietic stem cell transplantation (allo-HSCT) in acute leukemia (AL) and its significance as molecular marker to dynamically monitor minimal residual disease (MRD). METHODS: Retrospectively analyzed those AL patients who underwent allo-HSCT in the First Hospital Affiliated to Zhejiang University School of Medicine during Jan 2016 to Dec 2017, a total number of 314 cases, 163 males and 151 females, median age was 30 (9–64) years old. Comparing the difference of WT1 expression at diagnosed, pre-HSCT and after HSCT. Using the receiver operating characteristic (ROC) curve to determine the WT1 threshold at different time so as to predict relapse. The threshold of WT1 expression before transplantation was 1.010%, within 3 months after HSCT was 0.079% and 6 months after HSCT was 0.375%. According to these thresholds, WT1 positive patients were divided into low expression groups and high expression groups. Analyzed the relationship between overall survival (OS), disease-free survival (DFS), cumulative incidence of relapse (CIR) and WT1 expression. RESULTS: The OS and DFS of high expression group pre-HSCT were lower than low expression group [69.2% (9/13) vs 89.1% (57/64), χ(2)=4.086, P=0.043; 53.8% (7/13) vs 87.5% (56/64), χ(2)=9.766, P=0.002], CIR was higher than low expression group [30.8% (4/13) vs 7.8% (5/64), P=0.017]. There was no significant difference of OS and DFS between high expression and low expression group of 3 months after HSCT (P=0.558, P=0.269). The OS and DFS of high expression group of 6 months after transplantation were both lower than low expression group (P=0.049, P=0.035). Multivariate analysis showed that WT1>0.375% when 6 months after transplantation was the only independent prognostic factor for shorter DFS (P=0.022). There was no statistically significant difference in CIR between the high-expression group and the low-expression group 3 months after transplantation and 6 months after transplantation (P=0.114, P=0.306). CONCLUSION: High expression of WT1 before and after HSCT was an adverse prognosis factor. It is of clinical practical value to use WT1 as a transplant recommendation index for patients with acute leukemia and as a marker to monitor MRD dynamically.